PENGARUH FUMIGASI MENGGUNAKAN AIR DAUN SIRIH TERHADAP DAYA TETAS TELUR DAN MORTALITAS EMBRIO TELUR PUYUH - P.N Jefri (Fakultas Pertanian Universitas Tamansiswa Padang, 2022)
This replacement of natural disinfectants is expected to improve fertility, increase hatchability, increase hatching weight and reduce mortality. This study aims to determine whether the fumigation of betel leaf water can improve fertility, increase hatchability, increase hatching weight and reduce mortality in quail hatching, as well as determine the best level of administration in a mixture of betel leaf water and aquades. This study used a completely randomized design (CRD) consisting of 5 treatments, namely p1 (Control), p2 (70% Alcohol), p3 (20 ml Betel Leaf Extract + 80 ml Aquades), p4 (30 ml Betel Leaf Extract + 70 ml Aquades ), and p5 (40 ml Betel Leaf Extract + 60 ml Aquades) and 4 replicates. The data obtained were processed using variance, if the results showed significant differences, they were tested using the Duncan multiple range test (DMRT). The results showed that quail eggs fumigated using Betel Leaf Extract had an average fertility ranging from 80.00 – 97.00%. The average hatchability ranged from 80.55– 96.91%. The average hatching weight ranged from 8.72 to 8.74 grams. And the average mortality ranged from 3.09 to 19.45%. The results of the study on the effect of treatment on fertility, hatchability and mortality showed a very significantly different effect (P<0.01). Meanwhile, on hatching weight, the effect was not significantly different (P>0.05). Based on the results of this study, it can be concluded that the most optimal fumigation using Betel Leaf Extract is treatment 3 (20 ml Betel Leaf Extract + 80 ml Aquades) with an average fertility of 97.00%, hatchability 96.91%, hatching weight 8.72 grams, and 3.09% motility.